People and their smartphones – mapping mobile interaction in the modern connected world. Issue 6 (1st August 2016) - Shen, Siu-Tsen
Abstract : Purpose: – The purpose of this paper is to investigate how a balanced study group consisting of 152 participants interact with, operate, customize, and control their smartphone applications. Design/methodology/approach: – This work uses a qualitative research methodology involving an online user study questionnaire, supported by e-mailed user screenshots and online conversations. Findings: – In terms of smartphone age, 72 per cent of the participants' smartphones were less than two years old. This high level of churn rate was anticipated and will please retailers and marketers alike. This study found that the majority of smartphone users regularly arrange their app icons and that their categorization principle was based primarily on application associated functionality and frequency of use. This group of users seemed less concerned about the risks of privacy and security, and even when they had lost or had their smartphone stolen, few (5.2 per cent) had suffered from fraud, in contrast to the general perception of risk. Originality/value: – This is one of the few studies to have investigated the area of smartphone use from the users' perspective, leading to important insights into application user behaviour and icon arrangement, and as well as alternative possible implications for launcher design.